Women's Economic Empowerment Through Microfinance Schemes Offered By Rural Banks In Surat District - Lakhesarani, Babita (Journal of Neonatal Surgery, 2025)
This research paper investigates the impact of microfinance schemes provided by rural banks in Surat District on women's economic empowerment. Utilizing qualitative analysis, the study explores how access to financial resources, capacity-building initiatives, and increased decision-making power contribute to enhancing women's livelihoods and socio-economic status. Findings reveal significant improvements in income generation, financial inclusion, and social empowerment among female microfinance beneficiaries. However, challenges such as limited access to credit and bureaucratic hurdles persist, underscoring the need for tailored interventions to address the specific needs of rural women. The study provides valuable insights for policymakers, practitioners, and stakeholders interested in promoting women's economic empowerment through microfinance interventions in rural areas